BACK-BONE OR BURDEN? THE ROLE OF THE RPS IN THE BRA. Issue 136 (April 2018) - Baker, Penelope
Abstract : The place of the Records Preservation Section (RPS) within the British Records Association (BRA) has come under regular scrutiny often at times of financial crisis. Using the BRA archives deposited at the London Metropolitan Archives, this article explores the changing role of the RPS over the last 85 years and its influence in the development of the Association and the broader archive sector.